Stabilisation of critically ill children at the district general hospital prior to intensive care retrieval: a snapshot of current practice. Issue 9 (9th August 2009) - Lampariello, S; Clement, M; Aralihond, A P; Lutman, D; Montgomery, M A; Petros, A J; Ramnarayan, P
Abstract : Objective: To describe current practice during stabilisation of children presenting with critical illness to the district general hospital (DGH), preceding retrieval to intensive care. Design: Observational study using prospectively collected transport data. Setting: A centralised intensive care retrieval service in England and referring DGHs. Patients: Emergency transports to intensive care during 2-month epochs from 4 consecutive years (2005–2008). Interventions: None. Main outcome measures: Proportion of key airway, breathing, and circulatory and neurological stabilisation procedures, such as endotracheal intubation, mechanical ventilation, vascular access, and initiation of inotropic agents, performed by referring hospital staff prior to the arrival of the retrieval team. Results: 706 emergency retrievals were examined over a 4-year period. The median age of transported children was 10 months (IQR, 18 days to 43 months). DGH staff performed the majority of endotracheal intubations (93.7%, CI 91.3% to 95.5%), initiated mechanical ventilation in 76.9% of cases (CI 73.0% to 80.4%), inserted central venous catheters frequently (67.4%, CI 61.7% to 72.6%), and initiated inotropic agents in 43.7% (CI 36.6% to 51.1%). The retrieval team was more likely to perform interventions such as reintubation for air leak, repositioning of misplaced tracheal tubes, and administration of osmotic agents for raised intracranial pressure. The performance of one or more interventions by the retrieval team was associated with severity of illness, rather than patient age, diagnostic group, or team response time (OR 3.62, 95% CI 1.47 to 8.92). Conclusions: DGH staff appropriately performs the majority of initial stabilisation procedures in critically ill children prior to retrieval. This practice has not changed significantly for the past 4 years, attesting to the crucial role played by district hospital staff in a centralised model of paediatric intensive care.